A Latin American, Portuguese and Spanish consensus on a core communication curriculum for undergraduate medical education. Issue 1 (December 2016) - García de Leonardo, Cristina; Ruiz-Moral, Roger; Caballero, Fernando; Cavaco, Afonso; Moore, Philippa; Dupuy, Lila; Pithon-Cyrino, Antonio; Cortés, Mª; Gorostegui, Marilen; Loureiro, Elizabete; Fontcuberta, Josep; Casasbuenas Duarte, Luis; et al.
Abstract Background To present learning outcomes in clinical communication for a Core Curriculum for medical undergraduate students in Latin America, Portugal and Spain (LAPS-CCC) and to establish an expert network to support a transnational implementation. Methods Through an iterative process, an international group of 15 experts developed an initial set of learning outcomes following a review and discussion of relevant international and local literature. A two-round Delphi survey involving 46 experts from 8 countries was performed. Quantative and qualitative analisis permited the definition of the final consensus. Results The initial proposal included 157 learning outcomes. The Delphi process generated 734 comments and involved the modification, deletion and addition of some outcomes. At the end of the process, a consensus was reached on 136 learning outcomes grouped under 6 competency domains with a high overall acceptance (95.1 %). Conclusions The learning outcomes of this proposal provide a guide to introduce, support and develop communication curriculae for undergraduate medical studies in the countries involved or in other Spanish- or Portuguese-speaking countries.